2016
DOI: 10.1103/physreva.94.012321
|View full text |Cite
|
Sign up to set email alerts
|

Fast control of semiconductor qubits beyond the rotating-wave approximation

Abstract: We present a theoretical study of single-qubit operations by oscillatory fields on various semiconductor platforms. We explicitly show how to perform faster gate operations by going beyond the universally-used rotating wave approximation (RWA) regime, while using only two sinusoidal pulses. We first show for specific published experiments how much error is currently incurred by implementing pulses designed using standard RWA. We then show that an even modest increase in gate speed would cause problems in using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…For a system like a double dot coherently coupled to a microwave resonator [30][31][32][33], it is essential to use a dressedstate model [34] in which the qubit electron(s) and the resonator photon(s) are both treated quantum mechanically [35][36][37][38][39]. If, instead, the quantum dot is driven via a classical field, one may employ either a semiclassical [40,41,42] or a fully quantum model. Both approaches are capable of describing corrections to the RWA, and have been used to describe strong driving in superconducting qubit systems [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…For a system like a double dot coherently coupled to a microwave resonator [30][31][32][33], it is essential to use a dressedstate model [34] in which the qubit electron(s) and the resonator photon(s) are both treated quantum mechanically [35][36][37][38][39]. If, instead, the quantum dot is driven via a classical field, one may employ either a semiclassical [40,41,42] or a fully quantum model. Both approaches are capable of describing corrections to the RWA, and have been used to describe strong driving in superconducting qubit systems [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…The exchange interaction, as a virtual tunneling process, is similarly modified by the ac driving [33,34]. Several qubit platforms employing a resonant exchange interaction have been studied both theoretically and experimentally [35][36][37][38]. Resonant exchange qubits based on double quantum dots in both GaAs/AlGaAs heterostructures [39] and Silicon [40], as well as on triple quantum dots [41,42] have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…The previous schemes with STA focused on the physical systems under the rotating‐wave approximation (RWA). However, many recent schemes about superconducting systems, optomechanical systems, semiconducting systems, Bose‐Einstein condensates, and NV centers have shown that, RWA may be invalid in the cases of ultra‐fast operations and ultra‐strong couplings. For example, Liu et al .…”
Section: Introductionmentioning
confidence: 99%
“…have demonstrated in a NV center that, when using a magnetic field with a frequency of 30MHz, RWA can not be used for a qubit control if the Rabi frequency larger than 15MHz. From these examples, RWA may be invalid in fast quantum information processing, thus the applications of previous schemes with STA would be limited. Therefore, it is worthwhile to study STA without RWA so that pulse design for fast quantum information processing could be more effective.…”
Section: Introductionmentioning
confidence: 99%